Hubungan Usia, Paritas, dan Pekerjaan Terhadap Resiko KEK Ibu Hamil Trimester 1 di Puskesmas Cilengkrang Bandung Tahun 2022 - Gina Shofi Halimah; Ratna Dwi Jayanti; Widati Fatmaningrum (Poltekkes Kemenkes Padang, 2022)
Nutrition has a major contribution to the life cycle, one of the nutritional problems of pregnant women is malnutrition, both macro and micro malnutrition which is manifested in chronic energy deficiency In Indonesian it’s KEK. KEK can cause premature, low birth weight, stunting and other complications, early detection can use indicator by measuring Upper Arm Circumference. The prevalence rate of KEK for pregnant women in Indonesian 17.3% nationally. The purpose this study was to analyze the relationship between age, parity, occupation with KEK risk. Method research used quantitative with a crosssectional approach. The sample this study was the entire population, 1st trimester pregnant women at the Cilengkrang Health Center from March 2020 to March 2022 who had complete medical record data. The independent variables in the study were age, parity, occupation, the dependent variable was KEK risk. Sampling used a total sampling technique who met the inclusion criteria, analyzed using Univariate Analysis and Bivariate analysis was carried out with the Chi Square statistical. The results of research on each variable p value<0.05. The conclusion is there is a relationship between age, parity, occupation with KEK for pregnant women in 1st trimester. Suggestions for pregnant women and pregnant women plan their pregnancies at reproductive age at 20 years to 35 years and must know the nutrition they need during pregnancy, to create a healthy pregnancy and minimize the risk of complications.